2019
DOI: 10.1186/s40463-019-0357-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of second hand smoke in patients with squamous cell carcinoma of the head and neck

Abstract: Background Active tobacco smoking is a well-known risk factor for head and neck malignancy, and strong evidence has associated tobacco as the main carcinogenic factor in squamous cell cancers of this region. Evidence supporting a carcinogenic effect of second-hand smoke (SHS) on head and neck organs in non-smokers was also demonstrated with results consistent with those for active smokers. There is little data on the effects of SHS in patients previously treated for squamous cell carcinomas of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
2
12
2
Order By: Relevance
“…This is very much in line with our results, where the OR is also higher with exposure at both places. In contrast to the results of Idris et al 15 , we could not determine any difference in the occurrence of recurrences in our patients with and without exposure to ETS. However, Zhang et al 14 and Idris et al 15 had evaluated patients with head and neck squamous cell carcinoma and in one study, only about half of the participants were patients with OSCC, and in the other study, no information was given on the percentage of patients with oral cancer.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is very much in line with our results, where the OR is also higher with exposure at both places. In contrast to the results of Idris et al 15 , we could not determine any difference in the occurrence of recurrences in our patients with and without exposure to ETS. However, Zhang et al 14 and Idris et al 15 had evaluated patients with head and neck squamous cell carcinoma and in one study, only about half of the participants were patients with OSCC, and in the other study, no information was given on the percentage of patients with oral cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…With the ETS-score it is possible to record a numerical value for each individual. Other case-control studies report a dose-response relationship for the degree of ETS exposure and describe secondhand smoke as an independent predictor of recurrence and survival in patients with head and neck cancer 14 , 15 . Zhang et al 14 found an increased OR for heavy ETS exposure (exposure at home and at work) in comparison to moderate ETS exposure (exposure only at home or at work) in their study group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, none of the trials included in this review reported second-hand smoke exposure, which may negatively impact patient outcomes and quit rates. 124 , 125 With the recent increased prevalence of electronic cigarettes and cannabis use, these additional forms of tobacco, nicotine, and combustibles exposure will also need to be assessed and evaluated in relation to cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) is recorded to be the 8th most commonly occurring form of cancer in the world, with a high mortality and morbidity rate [1,2]. Approximately 600,000 new HNSCC cases and 350,000 HNSCC-related deaths take place every year across the globe [3][4][5]. Though many new techniques have been developed for diagnosing the patients during their early stages, more than half of the HNSSC patients are diagnosed only in their advanced stages [6].…”
Section: Introductionmentioning
confidence: 99%